2013
DOI: 10.1177/0748233713491808
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evaluation of methanolic leaf extract of Swietenia mahagoni on acrylamide-induced neuropathic pain in rats

Abstract: The present study was designed to investigate the antinociceptive effects of methanolic leaf extract of Swietenia mahagoni (MESM) on acrylamide-induced painful neuropathy in rats. The intraperitoneal administration of acrylamide (30 mg/kg; for 24 consecutive days) has been employed for the induction of painful neuropathy. Acrylamide induced nociceptive pain sensitive changes, which have been assessed by hot plate, Von Frey Hair, and tail immersion tests at different time intervals, that is, 0, 6, 12, 18, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…Thus, the paw pain threshold of acrylamidetreated rats in the present study was significantly reduced, indicating an impairment in the nociceptive system. The current findings are also in line with the results of a rat study by Vanitha et al (2015), in which the intraperitoneal administration of acrylamide at a dose of 30 mg/kg for 24 days resulted in sciatic neuropathy manifested in the development of thermal hyperalgesia and mechanical allodynia with a decreased hind paw pain threshold. Similarly, Ling et al (2005) demonstrated that low doses of acrylamide (max, 30 mg/kg/day) and a cumulative dose (<250 mg/kg) that did not cause motor dysfunction led to mechanical and thermal allodynia and hyperalgesia.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the paw pain threshold of acrylamidetreated rats in the present study was significantly reduced, indicating an impairment in the nociceptive system. The current findings are also in line with the results of a rat study by Vanitha et al (2015), in which the intraperitoneal administration of acrylamide at a dose of 30 mg/kg for 24 days resulted in sciatic neuropathy manifested in the development of thermal hyperalgesia and mechanical allodynia with a decreased hind paw pain threshold. Similarly, Ling et al (2005) demonstrated that low doses of acrylamide (max, 30 mg/kg/day) and a cumulative dose (<250 mg/kg) that did not cause motor dysfunction led to mechanical and thermal allodynia and hyperalgesia.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, proinf lammatory cytokines have been suggested to play a role in the pathogenesis of acrylamide neuropathy as well as reactive oxygen species (ROS) and oxidant products (Yan et al, 2019;Elblehi, El Euony, El-Sayed, 2020). Moreover, Vanitha et al (2015) showed that acrylamiderelated neuropathic pain and damage were reduced with antioxidant treatment. Goudarzi et al (2019) found that ellagic acid protected nerve tissue from the acrylamide oxidative and proinflammatory damage by inhibiting the acrylamide-induced increase of oxidants, tumor necrosis factor (TNF-α), and interleukin-1 beta (IL-1β) in the cerebral cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings revealed that alteration of a neuronal microvascular system is primary cardinal signs for the damage and degeneration of the nervous system [[68], [69], [70]]. Furthermore, some of our studies and other laboratory reports recommended that plant extracts and nutritional products of Acorus calamus [51,70], Butea monosperma [71], Swietenia mahagoni [72], Ocimum sanctum [73] and Vernonia cinerea [74] mitigate neuropathic pain symptoms. Phytoconstituents like puerarin [75], bulleyaconitine A [76], thymoquinone, epigallocatechin gallate, lycopene and resveratrol [17] produced an anti-neuralgic effect.…”
Section: Discussionmentioning
confidence: 88%
“…It also leads to an increase in the vulnerability of cell membrane and cellular damage and it will eventually lead to neurodegenerative lesions in the brain [14]. Acrylamide induces the oxidative stress associated with enhancement of neuronal intracellular calcium ion concentration along with neurodegeneration [28].…”
Section: Discussionmentioning
confidence: 99%